2012
DOI: 10.5455/gmj-30-2012-73
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the pattern of drug prescribing in pediatrics ward in tertiary setting hospital in Addis Ababa, Ethiopia

Abstract: Drugs have to be safe, effective and be used nationally and may require a special concern due to their unwanted side effects. Safely and effective use of drugs depend on prescribing pattern. The aim of the study was to assess the drug prescribing practice in pediatrics ward of St. Paul Specialized Hospital in Addis Ababa, Ethiopia. A retrospective study had been conducted from January 20 to February 15, 2009. Structured data collection formats were used to obtain data from patient records using stratified and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…This is important particularly in paediatric population and when one consider the high % of encounters (44.6%) with antibiotics. Such use of antibiotics is similar to 43.19% in India [36], much higher than (21%) reported for Omani pediatric population [37] and less than (53.42%) reported in Ethiopia [21]. It is a fact that antibiotics are routinely used for the treatment of pediatric illnesses and still irrationally used for inappropriate indications such as upper respiratory tract infections, acute otitis media and acute gastroenteritis.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…This is important particularly in paediatric population and when one consider the high % of encounters (44.6%) with antibiotics. Such use of antibiotics is similar to 43.19% in India [36], much higher than (21%) reported for Omani pediatric population [37] and less than (53.42%) reported in Ethiopia [21]. It is a fact that antibiotics are routinely used for the treatment of pediatric illnesses and still irrationally used for inappropriate indications such as upper respiratory tract infections, acute otitis media and acute gastroenteritis.…”
Section: Discussionmentioning
confidence: 55%
“…In the present study, the average number of drugs per encounter was 2.6. This is higher than the recommended figure of 2, however, it is similar to 2.5 in India [2], more than that in Ethiopia [21] but less than that in KSA [22]. Prescribing large number of drugs to a child increases the risk of adverse effects, drug interactions, dispensing errors and leads to less understanding of parents of dosages regimens [23] [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, all dispensed medicines were improperly labeled in Cambodia [ 31 ] and only1.4 % of prescriptions was adequately labeled in Nepal [ 3 ]. The study also showed that, 69.0 % of patients were able to repeat the correct dosage schedule of the medicine they had received which was relatively lower when compared to the other studies conducted in south west Ethiopia which were 79 and 72.80 % [ 19 , 22 ], but higher than a study conducted in Cambodia [ 30 ].…”
Section: Discussionmentioning
confidence: 62%
“…Enough studies were performed to investigate the prescribing trends in adults [ 10 , 11 ], whereas pediatricians lack such detailed information on most of the drugs [ 12 , 13 ]. Therefore, children are very vulnerable to possible harmful drug effects, and there are not enough studies on drug use in children [ 2 ].…”
Section: Introductionmentioning
confidence: 99%